Dickkopf-3 Acts as a Modulator of B Cell Fate and Function - Ludwig, Julia; Federico, Giuseppina; Prokosch, Sandra; Kueblbeck, Guenter; Schmitt, Sabine; Klevenz, Alexandra; Groene, Hermann-Josef; Nitschke, Lars; Arnold, Bernd (Journal of Immunology, 2015)
The mechanisms responsible for the generation of a mature B1 and B2 cell compartment are still poorly understood. In this study, we demonstrated that absence of Dickkopf-3 (DKK3) led to changes in the composition of the B cell compartment, which were due to an altered development and maintenance program of B cells. Development of B2 cells was impaired at the pre- and immature B cell stage, resulting in decreased numbers of follicular B cells in adult DKK3-deficient mice. Furthermore, DKK3 limited B1 cell self-maintenance in the periphery, by decreasing the survival and proliferation behavior of B1 cells. DKK3 may act via the BCR signaling pathway, as Ca2+ influx upon BCR stimulation was increased and SiglecG, a molecule shown to inhibit Calcium signaling, was downregulated in the absence of DKK3. DKK3-deficient mice exhibited altered Ab responses and an increased secretion of the cytokine IL-10. Additionally, DKK3 limited autoimmunity in a model of systemic lupus erythematosus. In summary, we identified DKK3 as a novel modulator interfering with B cell fate as well as the maintenance program of B cells, leading to changes in B cell immune responses.